2021
DOI: 10.1021/acs.energyfuels.1c03552
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Diffusion and Dispersion in Porous Media: Review of Advances in Experimental Measurements and Mathematical Models

Abstract: CO 2 molecular diffusion in subsurface porous media is one of the key mechanisms in high-pressure−high-temperature CO 2 geosequestration and CO 2 -based enhanced oil recovery projects. The mass transfer rate of injected supercritical CO 2 and its dissolution in reservoir fluids are mainly described by the gas diffusion coefficient. Over the past decades, numerous efforts have been made to investigate the CO 2 molecular diffusion process in both hydrocarbon reservoirs and saline aquifers. However, various exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 148 publications
(250 reference statements)
2
15
0
Order By: Relevance
“…Published matrix tortuosity values at similar spatial scales are the most directly comparable as reviews of previous studies have observed scale dependence in field measurements, similar to the scale dependence observed for dispersion . At the laboratory scale, the typical approach for the quantification of diffusion relies on bulk measurements of gas diffusion into or through samples and corresponding analytical model fits. , The methods in this study are analogous to these approaches, with the exception that an analytical model can be applied to every voxel of the image-based data, as opposed to typical bulk sample-average measurements. This image-based method results in hundreds of measurements of the matrix tortuosity in a given sample.…”
Section: Discussionsupporting
confidence: 62%
“…Published matrix tortuosity values at similar spatial scales are the most directly comparable as reviews of previous studies have observed scale dependence in field measurements, similar to the scale dependence observed for dispersion . At the laboratory scale, the typical approach for the quantification of diffusion relies on bulk measurements of gas diffusion into or through samples and corresponding analytical model fits. , The methods in this study are analogous to these approaches, with the exception that an analytical model can be applied to every voxel of the image-based data, as opposed to typical bulk sample-average measurements. This image-based method results in hundreds of measurements of the matrix tortuosity in a given sample.…”
Section: Discussionsupporting
confidence: 62%
“…78 The lack of consensus in predicting the phase behavior of shale oil via EOS makes further studies essential to improve understanding of these complex systems. 79 Energy & Fuels A brief overview of several empirical correlations and ML models for predicting the main PVT properties is provided in Table 1. Most of the correlations in this review do not use oil compositions as inputs; instead, they rely upon more general parameters such as specific gravity.…”
Section: Shale Oil Pvt Experimentsmentioning
confidence: 99%
“…It was found that the bubble-point pressure in the bulk region increased slightly . The lack of consensus in predicting the phase behavior of shale oil via EOS makes further studies essential to improve understanding of these complex systems …”
Section: Phase Behavior Of Shale Oilmentioning
confidence: 99%
“…Several recent reviews have discussed the advances of understanding phase behaviors, molecular diffusion, and miscibility during CO 2 -EOR in tight formations. These reviews provided rich information on CO 2 -EOR technologies but did not focus on microscopic interactions of CO 2 with fluids and minerals in shale.…”
Section: Introductionmentioning
confidence: 99%